Dose-effect calibration curve for high X-ray doses using the Calyculin-A chromosome premature condensation assay - Fabio-Andrés Chaves-Campos; Fernando Ortíz-Morales; Ricardo Mejías-Gamboa; Jorge Ernesto González-Mesa; Omar García-Lima; Maria Paula Rodríguez-Valerio; Walter Vargas-Segura; Anthony Cordero-Ramírez (Brazilian Journal of Radiation Sciences, 2024)
Purpose: This article shows the results of the Cytogenetics Laboratory of the Health Research Institute (INISA) to develop a dose-effect calibration curve with the Calyculin-A chemical induction premature condensation assay to estimate high doses of X-ray exposure. Methods: to create the calibration curve, peripheral blood samples from two participants (one female and one male) were exposed to X-rays at six different dose points ranging from 0 to 17.5 Gy in vitro. The irradiated blood was cultured for 48 hours according to international protocols, and the resulting chromosome rings were recorded. We used BioDoseTools software to calculate the coefficients for the calibration curve. Results: The coefficients of the curve are α: 0.028±0.001 and C: 0.001±0.001. These coefficients have similar values to those reported internationally. The curve was validated by calculating an unknown dose exposed to 6 Gy; the estimated dose was 5.651 ± 0.636 Gy, with no statistically significant differences between the dose delivered and the estimated dose. Conclusions: The INISA Biological Dosimetry Service can use the curve obtained to assess absorbed doses in cases of suspected overexposure to high X-ray doses.